Commodity Transport Studies Food Grains - Planning Commission (Planning Commission, 1968)
The food grains covered by the transport study of food grains are rice, wheat, jowar, gram and pulses which account for more than 80% of the total production of food grains in India in recent years. The geographical distribution of production and consumption of different food grains varies with the grain. The cultivation of rice is concentrated mostly in the States of Andhra Pradesh, Assam, Bihar, Kerala, Madhya Pradesh, Madras, Maharashtra, Mysore, Orissa, Uttar Pradesh and West Bengal which together account for about 95% of the country's production. The all-India growth rate for rice is estimated at 3.64% per annum.
Joint Technical Group for Transport Planning, Planning Commission
Joint Technical Group for Transport Planning, Planning Commission